Identifying Deteriorating Patients Through Multidisciplinary Team Training. (November 2016) - Merriel, Abi; van der Nelson, Helen; Merriel, Sam; Bennett, Joanne; Donald, Fiona; Draycott, Timothy; Siassakos, Dimitrios
Multidisciplinary training has improved maternity outcomes when the training has been well attended, regular, in house, used high-fidelity simulators, and integrated teamwork training. If these principles were used in other settings, better clinical care may result. This before-after study sought to establish whether a short multidisciplinary training intervention can improve recognition of the deteriorating patient using an aggregated physiological parameter scoring system (Early Warning Score [EWS]). Nursing, medical, and allied nursing staff participated in an hour-long training session, using real-life scenarios with simple tools and structured debriefing. After training, staff were more likely to calculate EWS scores correctly (68.02% vs 55.12%; risk ratio [RR] = 1.24, 95% confidence interval [CI] = 1.07-1.44), and observations were more likely to be performed at the correct frequency (78.57% vs 68.09%; RR = 1.20, 95% CI = 1.09-1.32). Multidisciplinary training, according to core principles, can lead to more accurate identification of deteriorating patients, with implications for subsequent care and outcome.